Oxidation of transition metal complexes with 3,7-diazabicyclo[3.3.1]nonane-derived ligands - Tarnai, Máté (2006)
A series of new 3,7-diazabicyclo[3.3.1]nonane (bispidone)-derived ligands with phenolic side chains were synthesized. The double Mannich condensation reaction to create the bicyclic bispidone was carried out successfully, though the isolation of the bispidones was not always straightforward. The preparation of the corresponding amine precursors was a very challenging task, which often led to more difficulties than the Mannich condensation itself. The preparation of the new bispidone ligands are described in Chapter 4. As structural models for the galactose oxidase enzyme, copper(II) complexes of the mononucleating phenol-bispidone ligands N2py2PhOH and vanilbis were prepared and structurally and spectroscopically investigated. These results are presented in Chapter 5. The crystal structure of the copper(II)-N2py2PhOH complex shows that the bispidone cavity is preorganized for copper(II) and that the incorporation of the phenolic moiety does not build up any strain in the ligand backbone (when compared to other known systems). The Cu(II)-N2py2PhOH complex disproportionates to a copper(I) salt and copper(II)-phenoxy radical. Dicopper(II) complexes with the dinucleating bispidone ligands cresbis and tBuBis, were designed as structural models of catechol oxidase (Chapter 5). A combined spectroscopic, magnetometric and computational study revealed that by tuning the reaction conditions (applying an organic base or a basic alumina in the synthesis), the distance between the copper(II) centers could be varied. Vanadyl-complexes with N2py2 and N2py2PhOH were also prepared and their spectroscopic properties compared to the known [V(IV)=O(N2py3o)]2+ complex (Chapter 6). Oxidation of the latter complex was shown to produce V(V)-oxo-peroxo species in high yields in methanol. To solve the inconsistency of the O-O distance and O-O stretching frequency for the side-on bound peroxo unit in the so formed [V(V)=O(O2)(N2py3o)]+ complex, a combined labeling and computational study was carried out. Further oxidation of this V(V)-oxo peroxo complex was possible using Ce4+, as indicated by the EPR spectra. A detailed spectrophotometric study was carried out to understand the nature of the reaction between the Co(II)-N2py2 complex with hydrogen peroxide (Chapter 7). The reaction products were both qualitatively and quantitatively analyzed using the hydrazine test reaction. Analogous reaction products were found when the complex of a structurally similar N2py2Bz ligand was used. Structural data obtained for complexes, which have been isolated from the reaction mixture, provided evidence on the dealkylation at the tertiary amine donor N7 in the ligand (Figure 1.3) Further details about the possible steps of the oxidative N-dealkylation were obtained from DFT calculations. From the results a mechanism was postulated (Figure 1.4). Moreover, the catalytic activity of Co(II)-N2py2 / H2O2 system in the oxidation of amines was investigated. Manganese(II) complexes of known bispidone-type ligands with N4 and N5 donor set were prepared and their reaction with hydrogen peroxide was studied, in order to ascertain whether there is analogy with divalent iron species and have catalytic activity in olefin oxidation. These results are presented in Chapter 8. Interesting spectroscopic features of the manganese complexes with phenol-bispidone ligands are also reported in this chapter. The UV-vis spectra of the manganese(III)-N2py2PhOH complex demonstrate slow decomposition and possible pathways are discussed.